2015
DOI: 10.1016/j.epsl.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Dead Sea drawdown and monsoonal impacts in the Levant during the last interglacial

Abstract: Sediment cores recovered by the Dead Sea Deep Drilling Project (DSDDP) from the deepest basin of the hypersaline, terminal Dead Sea (lake floor at ∼725 m below mean sea level) reveal the detailed climate history of the lake's watershed during the last interglacial period (Marine Isotope Stage 5; MIS5). The results document both a more intense aridity during MIS5 than during the Holocene, and the moderating impacts derived from the intense MIS5e African Monsoon. Early MIS5e (∼133-128 ka) was dominated by hypera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 55 publications
2
97
0
Order By: Relevance
“…10). At the same time the Dead Sea had elevated water levels (Torfstein et al, 2015), in agreement with the humid climate inferred for the eastern Mediterranean and increased Nile floods, leading to the formation of sapropel S5 (Grant et al, 2012). For the period of 128 to 123 ka Milner et al (2012) have suggested pronounced seasonality with increased summer aridity and winter precipitation on the basis of acicular aragonite formation (indicating enhanced evaporation) in an otherwise aquatic phase of the Tenaghi Philippon peatland (NE Greece).…”
Section: Fig 11supporting
confidence: 53%
“…10). At the same time the Dead Sea had elevated water levels (Torfstein et al, 2015), in agreement with the humid climate inferred for the eastern Mediterranean and increased Nile floods, leading to the formation of sapropel S5 (Grant et al, 2012). For the period of 128 to 123 ka Milner et al (2012) have suggested pronounced seasonality with increased summer aridity and winter precipitation on the basis of acicular aragonite formation (indicating enhanced evaporation) in an otherwise aquatic phase of the Tenaghi Philippon peatland (NE Greece).…”
Section: Fig 11supporting
confidence: 53%
“…The mean annual precipitation is 50 mm, usually falling in a few rainfall events per year. Past climatic records indicate that during glacial and interglacial periods between MIS 6 and MIS 4 the central Negev was mostly dry (Amit et al 2006;Vaks et al 2007), whereas short humid episodes (Negev Humid Periods, (2017) NHP), possibly resulting from a northern shift of the African Monsson system, occurred during interglacial times (Blome et al 2012;Kutzbach & Liu 1997;Larrasoaña et al 2013;Torfstein et al 2015;Vaks et al 2010). The last of the NHP (NHP-1) is dated to 142-109 ka and was synchronous with pluvial periods in the Sahara, the Egyptian Desert and the Arabian Peninsula (Osborne et al 2008;Osmond & Dabous 2004;Petit-Maire et al 2010;Rosenberg et al 2011;Yehudai et al 2017;Vaks et al 2006;.…”
Section: Geographic and Climatic Backgroundmentioning
confidence: 99%
“…A 40 m halite-dominant core was dated to 110-120 ka at a level of 235 m below the DS bottom ("blb"). Torfstein et al (2015a) related this to a sudden and rapid drawdown of the DS level. Katz and Starinsky (2015) commented by rejecting this interpretation, based on geochemical parameters.…”
Section: Dead Sea Deep Drilling Corementioning
confidence: 99%